Office Employees' Perception of Workspace Contribution: A Gender and Office Design Perspective. Issue 9 (November 2019) - Bodin Danielsson, Christina; Theorell, Töres
In this exploratory study, we investigated the relationship between office design and employee perception of its contribution to job satisfaction, comfort, and performance. The study includes 4, 352 employees in seven different office designs. Associations between workspace satisfaction and perceived access to supportive facilities (ancillary spaces for concentrated work and for different meetings) were also investigated since these factors may be related to employees' workspace satisfaction. Multivariate linear and logistic regression analyses were performed separately for men and women with adjustments for age and education. Supplementary correlation analyses were performed between workspace satisfaction and perceived access to supportive facilities. Results showed differences between employees' workspace satisfaction in studied office designs. Those with the lowest ratings of access to supportive facilities reported the lowest degree of satisfaction. The best results were found in cell-offices and the worst ones in hot-desking offices. Gender differences were also observed.